Integration of Vertical Electric Sounding (VES) and Standard Penetration Test (SPT) for Geotechnical Investigation of Subsurface in Phuket - Keo, Solina (Prince of Songkla University, 2023)
Thesis (M.Sc., Earth System Science)--Prince of Songkla University, 2022